2015
DOI: 10.1590/0100-3984.2014.0002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound scan as a potential source of nosocomial and cross-infection: a literature review

Abstract: The authors review the main concepts regarding the importance of cleaning/disinfection of ultrasonography probes, aiming a better comprehension by practitioners and thus enabling strategies to establish a safe practice without compromising the quality of the examination and the operator productivity. In the context of biosafety, it is imperative to assume that contact with blood or body fluids represents a potential source of infection. Thus, in order to implement cleaning/disinfection practice, it is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…These viruses can also spread from mothers to babies during normal vaginal delivery, which might result in the development of recurrent respiratory papillomatosis (RRP) in the child, a rare condition where warts caused by HPV form in the respiratory tract [2,3]. Iatrogenic HPV infections have also been reported in the healthcare setting, especially via vaginal ultrasound transducers and other re-usable gynecological equipment [4].…”
Section: Introductionmentioning
confidence: 99%
“…These viruses can also spread from mothers to babies during normal vaginal delivery, which might result in the development of recurrent respiratory papillomatosis (RRP) in the child, a rare condition where warts caused by HPV form in the respiratory tract [2,3]. Iatrogenic HPV infections have also been reported in the healthcare setting, especially via vaginal ultrasound transducers and other re-usable gynecological equipment [4].…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations build on the original guidelines created by Earlie H. Spaulding, 4 who detailed a key classification scheme for disinfection and sterilization. However, despite available international guidelines for ultrasound cleaning, it has been reported that 87% of academic medical centers do not have a mandated protocol or standard contact time for transducer disinfection . By definition, there are 2 types of disinfection: high level and low level.…”
Section: Literature Comparison For Ultrasound Cleansingmentioning
confidence: 99%
“…Step five is “etiology explored.” Diagnose the etiology by integrating the above four steps; search for the source of infection according the clues extracted from the focused ultrasound exam; additional ultrasound exams or other tests should applied if needed. The clues are listed as examples: acute cor pulmonale indicates pulmonary embolism, unreasonable ventilation setting, or severe mismatch of the ventilation and flow representing ARDS [ 45 ]; acute increase in PAOP derives from decrease in systolic function, left side valve insufficiency, hypervolemia, or decreased myocardium compliance [ 66 ]; diffuse sonointerstitial syndrome (SIS) indicates hypervolemic pulmonary edema, cardiogenic pulmonary edema, leakage pulmonary edema, acute pneumonitis, pulmonary alveolar proteinosis, and chronic pulmonary fibrosis [ 6 , 37 , 67 ]; consolidation with shred sign in lung ultrasound indicates pneumonia [ 68 70 ]; hypoechoic yet heterogeneous at plural cavity indicates hemothorax or pyothorax [ 32 , 33 ]; echogenic dots in free fluid indicate abscessus [ 33 , 71 ]; echogenic dots in physiology cavity indicate infection [ 33 , 71 ] and so forth. With the clues above, we can clearly know what to do next and the diagnosis procedure can be efficient.…”
Section: The Piepear Workflow: a Critical Care Ultrasound Based 7-mentioning
confidence: 99%
“…With the clues above, we can clearly know what to do next and the diagnosis procedure can be efficient. Guiding the diagnosis of the etiology and source searching is a remarkable competence of critical care ultrasound [ 32 ]. However, the other exams are strongly required in the diagnosis procedure, and critical care ultrasound is more like a guide.…”
Section: The Piepear Workflow: a Critical Care Ultrasound Based 7-mentioning
confidence: 99%